Baudrillard. Philosophy of Seduction - Tillería Aqueveque, Leopoldo (2019)
The article discusses the problematic concept of seduction in the work of the sociologist and French philosopher Jean Baudrillard, lodged particularly in his book Seduction (1979). Proposes a nature of ontological even if not metaphysical for baudrillardian seduction, in which the self has no place but as pure symbolic domain of forms. The work is also based on the criticism of the Chilean philosopher Cristóbal Holzapfel, for whom the seduction absorbed the sense of things. Held that seduction is not sexual, love, pornographic, or digital in nature. Nor is flirting, affair, or a romantic approach, simply because the seduce operates by reversible eroticism. In the end, there are several aesthetics of seduction: the seduction as ghost, illusion, as death and play strange modes of an essentially heterodox seduction.